2010
DOI: 10.18272/aci.v2i2.35
|View full text |Cite
|
Sign up to set email alerts
|

EOT sub-nanométrico y degradación de la movilidad: ¿hacia un límite físico con las técnicas de fabricación modernas?

Abstract: In this article we investigate the major problem of the micro/nano-electronic: How to reduce the Equivalent Oxide Thickness (EOT) in the sub-nanometric range and improving the MOSFET performance? To reduce the EOT it is necessary that the semiconductor industry introduce the high-κ material as the Hafnium (Hf) in the dielectric layer. However the Hf produces a reduction of the mobility and therefore a reduction of the MOSFET speed. We explain through a simple semi-empirical model this mobility degradation in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Ongoing MOSFET scaling has led to consider new architecture like FinFET (FF), three dimensional devices with new dielectric materials such as high dielectric constant (high-k) materials [2,3]. This has implied further reduction of contact dimensions, which now reaches diameters of less than 50 nm [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing MOSFET scaling has led to consider new architecture like FinFET (FF), three dimensional devices with new dielectric materials such as high dielectric constant (high-k) materials [2,3]. This has implied further reduction of contact dimensions, which now reaches diameters of less than 50 nm [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These "nano vias" are of the utmost importance to get the best performance of the FF, mainly because of series resistance and parasitic capacitance considerations. Recently, during several failure tests, it has been observed that copper nano vias are literally destroyed (Figure 1) under high fluence stress [1][2][3][4][5][6]. This may find an explanation by localized heating due to Joule effect, but first order calculations based on simplified thermal considerations show rather low temperature in order to explain void presence in the nano vias, which such be over, at least, copper silicate formation temperature (823 K) [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%